Investigation of Forming Behaviour of Metal-Polymer Sandwich Composite through Limit Dome Height Test Simulations - Tsegaye Bekele; Perumalla Janaki Ramulu; Habtamu Beri; Amrela Siraji; P. Praveen Kumar Reddy (Journal of Engineering)
Metal-polymer-metal (MPM) sandwich composites are in the class of proficient engineering materials which give outstanding strength-to-weight ratios because of their comparatively low density. These materials are vital constituents within the automobile, aerospace, marine, and civil construction industries as substitutes for sheet metals that considerably reduce weight while not compromising functionality. Moreover, these materials have supplementary qualities like sound dampening and thermal insulation capabilities. For these materials to be utilized within the aforesaid industries, they need to bear numerous forming processes that are essential in product manufacturing. This paper investigated formability analysis of metal-polymer sandwich composites made of “AW 6082-PVC-AW 6082 (APA)” and “galvanized steel-PVC-galvanized steel (GPG)” sandwich sheets, considering epoxy structural adhesives as the binding agent, via FEA simulation. All the FEA simulations were performed using Altair HyperWorks software. For evaluating the formability, the actual limit dome height (LDH)—biaxial strain path—tests were simulated using FEM software. The results analyzed are forming limit diagram (FLD), punch force distribution, and a dome height at diverse conditions of punch velocity and friction. A comparison is made to represent the best combinations for formability of the sandwich composites. Maximum formability and dome height are attained at low friction conditions and forming speed. It has also been observed that LDH simulations are very sensitive to friction, and it has a substantial impact on the test outputs. Maximum thinning (or fracture) generally moves away from the apex of the dome towards the die corner radius as the friction increases from zero upwards.